Opozycja */u/ : */uː/ w gwarze Jastarni - Jocz, Lechosław (Slavia Occidentalis, 2019)
The paper is devoted to the reflexes of the old contrast between */u/ and */uː/after labials and velars and in a front position in a word in the Kashubian dialect spoken in Jastarnia. According to descriptions from the late 19th century and the early 20th century, the contrast was preserved at the beginning of a word and in the middle of a word as contrasted with the quantity and quality (with a probable weakening of the first component of the contrast): [u̯ɘ̟] : [u(ː)]. At the end of the word, the contrast was weak and disappeared. According to sources from the mid-20th century, the contrast has been entirely lost in all the positions and [u̯ɘ̟] and [u] are merely free variants of one phoneme /u/. However, an analysis of contemporary material shows clearly that the old contrast was preserved word-initially and word-internally with some cases of simple morphological levelling. Two phonemes, /ʉ/ and /u/, need to be assumed. The current system is strongly correlated with a system documented in the oldest descriptions and could not develop secondarily from a hypothetical system which would merge */u/ and */uː/ to any extent exceeding a free variation in some forms while morphological levelling took place. It seems that the conclusions offered in the publications from the mid-20th century (refuting the existence of the contrast) had an irrational (personal and maybe national) background.